The impact of PBD (plant-based diet) on atherosclerosis biomarkers in the risk and progression of coronary heart disease: A systematic review of randomized controlled trials - Shafrina, Amara Azka; Hakiki, Riski; Sari, Raudhah; Ramadhani, Yasmin Nabila; Nauval, Iflan (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2025)
ABSTRACTBackground: Coronary heart disease (CHD) is a leading cause of premature death globally. Plant-based diet (PBD), which emphasizes vegetables, fruits, legumes, grains, oils, and nuts with minimal animal products, is gaining attention for its potential cardiovascular benefits. It may impact atherosclerosis progression by improving lipid profiles, inflammation, blood pressure, and endothelial function.Objective: This review evaluates the effects of PBD on atherosclerosis biomarkers in at-risk individuals and CHD patients.Methods: A systematic review of randomized controlled trials (RCTs) published between 2019 and 2024 was conducted using keywords: